Sejarah Kehidupan Nabī Dalam Musnad Aḥmad: Kajian Analitik Ayat Al-Qur’ān Tentang Sīrah Nabawiyyah - Siregar, Idris; Harahap, Alwi Padly (Jayapangus Press, 2024)
A review of early Islamic sources confirms that several verses of the Qurān are considered by Muslim scholars to be sources for the history of the Prophet’s early life. However, modern scholars argue about the suitability of this verse of the Qurān as a carrier of true biographical information about the Prophet. Because hadith are considered as an interpretive tool to dig deeper into the meaning of the Al-Qurān, and one of them contains a very extensive source of information about the life of the Prophet, it is very necessary to analyze the ḥadīṡ-ḥadīṡ about the Nabawiyyah sīrah. This research aims to explore the history of the Prophet's early life in Musnad Aḥmad and analyze Aḥmad's perspective regarding verses in the Al-Qurān about the Prophet's early life. This research is qualitative in nature where the researcher uses a critical and analytical approach as the methodology. This study finds that the scarcity of Quranic verses regarding Muhammad’s early life in the Musnad Ahmad, a vast inventory of hadith dating to the ninth century, indicates a scholar’s view of Muhammad’s early life. It is clear that Aḥmad did not relate the Qur’ān to the narrative of the Prophet’s early life, even though the verses are widely used by sīrah writers as descriptions of Muhammad’s early life.